Enteropathogenic Escherichia coli Inhibits Type I Interferon- and RNase L-Mediated Host Defense To Disrupt Intestinal Epithelial Cell Barrier Function - Long, Tiha M. (American Society for Microbiology, 2014)
Enteropathogenic Escherichia coli (EPEC) primarily infects children in developing countries and causes diarrhea that can be deadly. EPEC pathogenesis occurs through type III secretion system (T3SS)-mediated injection of effectors into intestinal epithelial cells (IECs); these effectors alter actin dynamics, modulate the immune response, and disrupt tight junction (TJ) integrity. The resulting compromised barrier function and increased gastrointestinal (GI) permeability may be responsible for the clinical symptoms of infection. Type I interferon (IFN) mediates anti-inflammatory activities and serves essential functions in intestinal immunity and homeostasis; however, its role in the immune response to enteric pathogens, such as EPEC, and its impact on IEC barrier function have not been examined. Here, we report that IFN-β is induced following EPEC infection and regulates IEC TJ proteins to maintain barrier function. The EPEC T3SS effector NleD counteracts this protective activity by inhibiting IFN-β induction and enhancing tumor necrosis factor alpha to promote barrier disruption. The endoribonuclease RNase L is a key mediator of IFN induction and action that promotes TJ protein expression and IEC barrier integrity. EPEC infection inhibits RNase L in a T3SS-dependent manner, providing a mechanism by which EPEC evades IFN-induced antibacterial activities. This work identifies novel roles for IFN-β and RNase L in IEC barrier functions that are targeted by EPEC effectors to escape host defense mechanisms and promote virulence. The IFN-RNase L axis thus represents a potential therapeutic target for enteric infections and GI diseases involving compromised barrier function.